Clinical and genetic features of childhood-onset congenital combined pituitary hormone deficiency: a retrospective, single-center cohort study - Yoonha Lee; Young Ah Lee; Jung Min Ko; Choong Ho Shin; Yun Jeong Lee (Annals of Pediatric Endocrinology & Metabolism)
Purpose To investigate the clinical characteristics and genetic features of childhood-onset congenital combined pituitary hormone deficiency (cCPHD) in Korean patients. Methods We retrospectively analyzed 444 patients diagnosed with childhood-onset CPHD at a tertiary center between 1994 and 2021. After excluding acquired case, 43 patients with cCPHD were enrolled. Anthropometric measurements, hormone evaluations, brain magnetic resonance imaging (MRI), extrapituitary phenotypes, and adult outcomes were analyzed. Genetic analyses were performed on 26 patients using a targeted gene panel or whole exome sequencing. Results Mean age at diagnosis was 3.2 years, and 41.9% were diagnosed at less than 1 year old. Short stature was the most frequent (37.2%) initial presentation, and mean height z-score was -2.4. More than half (n=23, 53.5%) of patients had neonatal features suggestive of hypopituitarism; however, only 15 (65.2%) were diagnosed in infancy. Growth hormone deficiency (GHD) was prevalent in 42 (97.7%), and 33 (76.7%) had 3 or more hormone deficiencies. Extrapituitary phenotypes were identified in 31 (72.1%). Brain MRI abnormalities correlated with a higher number of hormone deficiencies (P for trend 0.049) and were present in 33 patients (80.5%). Adult GHD was diagnosed in all 17 investigated patients, and metabolic disturbances were noted in 10 (58.9%). Pathogenic variants in POU1F1, GLI2, HESX1, TBC1D32, and ROBO1 were found in 5 (19.2%). Conclusions Considering the high proportion of neonatal presentations, identification of the early neonatal features of hypopituitarism to manage pituitary and extrapituitary phenotypes is critical. The genetic etiology of cCPHD warrants further exploration.